Study of Etiological factors, mycological profile and treatment of Otomycosis - Vincent Prasanna; V M Hemlata Katiyar; I. Kannan (International Journal of Medical Research and Review, 2014)
Introduction: Otomycosis is a common condition encountered in ENT practice. Though it is not a serious condition it causes a lot of misery to the patient. Though there are many studies on various aspects about this disease, there are not many studies from this part of the country.Materials and Methods: 75 patients attending ENT OPD and diagnosed to have otomycosis were included in the study. Two aural swabs or whenever possible otomycotic debris scooped out using Jobson –Horne probe was obtained. From one swab, wet mount preparation in 10% KOH (potassium hydroxide) solution and smear for Grams stain were prepared. The second swab / otomycotic debris was directly inoculated into SDA (sabourad’s dextrose agar) medium.Results: Mycological analysis of the swab from external auditory canal showed that Aspergillus species was the most common fungus isolated followed by Candida species. All patients were treated with regular suction clearance and 1% clotrimazole ear drops.Conclusion: avoiding usage of ear buds/ unsterile material will help in prevention of otomycosis. 1% clotrimazole is effective in achieving complete mycological cure in otomycosis. Regular long term follow-up is required to effectively treat otomycosis.